Anti-disturbance rapid vibration suppression of the flexible aerial refueling hose. (1st May 2018) - Su, Zikang; Wang, Honglun; Li, Na
Highlights: A finite-time convergence NFTSM observer is established to estimate the disturbances. A back-stepping based FTSMC controller is proposed for the PMSM servo tracking system. Rapid anti-disturbance vibration suppression scheme is proposed for the flexible hose. Abstract: As an extremely dangerous phenomenon in autonomous aerial refueling (AAR), the flexible refueling hose vibration caused by the receiver aircraft's excessive closure speed should be suppressed once it appears. This paper proposed a permanent magnet synchronous motor (PMSM) based refueling hose servo take-up system for the vibration suppression of the flexible refueling hose. A rapid back-stepping based anti-disturbance nonsingular fast terminal sliding mode (NFTSM) control scheme with a specially established finite-time convergence NFTSM observer is proposed for the PMSM based hose servo take-up system under uncertainties and disturbances. The unmeasured load torque and other disturbances in the PMSM system are reconstituted by the NFTSM observer and to be compensated during the controller design. Then, with the back-stepping technique, a rapid anti-disturbance NFTSM controller is proposed for the PMSM angular tracking to improve the tracking error convergence speed and tracking precision. The proposed vibration suppression scheme is then applied to PMSM based hose servo take-up system for the refueling hose vibration suppression in AAR. Simulation results show the proposed scheme can suppress the hose vibration rapidly and accurately even the system is exposed to strong uncertainties and probe position disturbances, it is more competitive in tracking accuracy, tracking error convergence speed and robustness.